Editorial (REVISTA NODO, 2021)
NODO is an academic journal edited by the School of Arts and the Vice-Rector for Science, Technology and Innovation at the Antonio Nariño University in Bogotá, Colombia. Its purpose is to further the progress of science by publishing new research articles, particularly those within three major fields: Architecture. Sustainable design, landscape architecture, architectural criticism and technology. The City. Physical aspects of human settlements (urban design, planning), and social and cultural phenomena taking place in towns (sociology, anthropology, communication, arts, music). The Environment. Biotic and abiotic components (flora, fauna and ecosystems; water, soil and air, respectively) from urban, suburban and regional areas. NODO is aimed at researchers, teachers, students and scholars from all fields of study devoted to the construction of better cities, both as architectural and urban assemblies, as well as social, cultural, environmental and ecological phenomena.